Evaluación de los riesgos psicosociales del teletrabajo desde la perspectiva de género en los docentes de la ESPAM-MFL en el periodo 2020 - 2021 - Basurto Calderón, Melany Concepción (2022)
The present investigation was oriented to the identification of psychosocial risk factors from a gender perspective on the teachers at Escuela Superior Politécnica Agropecuaria de Manabí "Manuel Félix López", with the objective of analyzing its main consequences in physical and mental health. The methodology was initially based on surveys of the actors involved, where the F-psycho questionnaire prepared by the National Institute of Safety and Health at Work was used, based on this, the incidence of these factors in each of the teachers was analyzed. Also, a comparative study between genders was applied to detect which of them had the greatest psychosocial affectation during teleworking. It is concluded that it is necessary for the institution to implement new measures to reduce the presence of these factors that negatively affect the family and work life of each individual, in effect, this study contributes positively to the university population. Subsequently, the mitigation plan was developed and shared with all the teachers, to explain the percentage of psychosocial risk that exits in each of them and the preventive measures that can be applied.